2019
DOI: 10.1371/journal.pone.0210360
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and associated factors of acute kidney injury among adult dengue patients: A retrospective single-center study

Abstract: Severe dengue cases have been increasingly reported in Thailand, and the under-reporting of acute kidney injury (AKI) in cases of dengue viral infection has become an obstacle in obtaining an accurate description of the true nature and epidemiology of AKI. Because AKI may lead to patient morbidity and mortality, an early diagnosis is important in preventing its onset in dengue patients. This study aimed to determine the prevalence, clinical and laboratory characteristics, and associated factors of AKI among ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(77 citation statements)
references
References 33 publications
3
69
3
2
Order By: Relevance
“…In our study, none of these—with the exception of HIV and CKDs—were associated with longer inpatient stay. Being immunocompromised has been described as a risk factor for severe dengue previously, 35 and renal disorders have also been linked to dengue severity; however, this has mostly referred to acute episodes rather than chronic conditions 45 …”
Section: Discussionmentioning
confidence: 99%
“…In our study, none of these—with the exception of HIV and CKDs—were associated with longer inpatient stay. Being immunocompromised has been described as a risk factor for severe dengue previously, 35 and renal disorders have also been linked to dengue severity; however, this has mostly referred to acute episodes rather than chronic conditions 45 …”
Section: Discussionmentioning
confidence: 99%
“…Acute kidney injury (AKI) and acute renal failure (ARF) are significant complications of dengue, and patients presenting SD are more likely to develop them [25,34,[36][37][38][39][40]. Rates of mortality due to AKI are 1% for classic dengue, 12-40% for DHF and 60% for DSS [41].…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective study among dengue patients reported a 14.2% incidence of AKI and identified independent predictive factors for developing AKI including DHF, multiorgan dysfunction and Diabetes Mellitus [8]. Although in comparison to other reports this high incidence may be reflective of sampling from a dengue "hotspot" in an endemic county, similar associated factors including severity of dengue fever, older age group, obesity, coexisting bacterial infection and hypoalbuminemia on admission have been noted [9]. Dengue should be considered a major contributor to the development of AKI among patients where the infection is endemic and the prevalence is greater.…”
Section: Discussionmentioning
confidence: 68%